Generic and Specific Roles of Saccharides at Cell and Bacteria Surfaces Revealed by Specular and Off-Specular X-Ray and Neutron Scattering - Schneck, Emanuel (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2011)
Systematic investigations of the structure, mechanics, and dynamics of biological surfaces help us understand more about biological processes taking place at cell and bacteria surfaces. Presented here is a study of the role membrane-bound saccharides play in the modulation of interactions between cells/bacteria and their environments. In this thesis, membrane structures were probed perpendicular and parallel to the surface, and sophisticated planar models of biomembranes composed of glycolipids of various structural complexities were designed. Furthermore, specular and off-specular X-ray and neutron scattering experiments were carried out. This research has led to the development of several new methods for extracting information on the structure and mechanics of saccharide-rendered biomembranes from the measured scattering signals. In fact, more is now known about the influence of the saccharide structure. These results demonstrate that the study of planar model systems with X-ray and neutron scattering techniques can provide comprehensive insight into the structure and mechanics of complex biological surfaces.